Q. 214.0( 2 Votes )

Mark the correct alternative in the following:

If in an A.P., the pth term is q and term is zero, then the term is

A. p

B. p

C. p + q

D. p q

Answer :

Here, ap=q and a(p+q)=0


i.e. a+(p-1)d=q______(1)


and a+(p+q-1)d=0_____(2)


Subtracting (1) from (2) we get,


qd=-q


d=-1


substituting this in (2) we get,


a+(p+q-1)(-1)=0


a=p+q-1


So, aq=a+(q-1)d


=p+q-1+(q-1)(-1)

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses